2020
DOI: 10.1038/s41524-020-0273-1
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the anchoring behavior in lithium-sulfur batteries: many-body effect on the suppression of shuttle effect

Abstract: We apply the state-of-the-art many-body dispersion (MBD) method to study the anchoring behavior in lithium-sulfur (Li-S) batteries, which is closely related to the notorious "shuttle effect". Based on the experimental results of metal sulfides (FeS and SnS 2 ), we find that the MBD method gives a more accurate prediction of anchoring mechanism compared with other van der Waals (vdW) inclusive methods. We systematically investigate the anchoring mechanism of two prototypal anchoring materials-Ti 2 CF 2 and dope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Lithium–sulfur (Li–S) batteries have attracted enormous interest in research due to their high capacity, high energy density, low cost, and environmental friendliness. However, their large-scale commercialization has been greatly limited by several obstacles, especially the notorious shuttle effect, , which is caused by the dissolution of lithium polysulfides (LiPSs) into the electrolyte. The shuttle effect of LiPSs will corrode lithium electrodes and significantly reduce the utilization of S and Coulomb efficiency, consequently resulting in self-discharge behavior and rapid capacity attenuation. , In recent years, tremendous efforts have been made toward designing the electrode structure and suppressing the shuttle effect to achieve a high cycling performance in Li–S batteries. One effective strategy is to adopt an anchoring material (AM) to capture LiPSs. The first choice was elemental carbon materials, which exhibit excellent electrical conductivity and were reported to improve the specific capacity and cycling performance of Li–S batteries, but the poor affinity between homoatomic nonpolar carbon materials and LiPSs will induce the detachment of LiPSs, resulting in poor cycling performance and irreversibility . Consequently, some polar materials were found to exhibit much stronger chemical interaction with LiPSs than carbon, such as metallic oxides, , transition-metal sulfides, and nitrides. , However, most of them have poor electrical conductivity, which limits their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium–sulfur (Li–S) batteries have attracted enormous interest in research due to their high capacity, high energy density, low cost, and environmental friendliness. However, their large-scale commercialization has been greatly limited by several obstacles, especially the notorious shuttle effect, , which is caused by the dissolution of lithium polysulfides (LiPSs) into the electrolyte. The shuttle effect of LiPSs will corrode lithium electrodes and significantly reduce the utilization of S and Coulomb efficiency, consequently resulting in self-discharge behavior and rapid capacity attenuation. , In recent years, tremendous efforts have been made toward designing the electrode structure and suppressing the shuttle effect to achieve a high cycling performance in Li–S batteries. One effective strategy is to adopt an anchoring material (AM) to capture LiPSs. The first choice was elemental carbon materials, which exhibit excellent electrical conductivity and were reported to improve the specific capacity and cycling performance of Li–S batteries, but the poor affinity between homoatomic nonpolar carbon materials and LiPSs will induce the detachment of LiPSs, resulting in poor cycling performance and irreversibility . Consequently, some polar materials were found to exhibit much stronger chemical interaction with LiPSs than carbon, such as metallic oxides, , transition-metal sulfides, and nitrides. , However, most of them have poor electrical conductivity, which limits their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to analyze the anchoring performance of the polypeptoid material, we have systematically investigated the binding energies of LiPSs on the surface of the polypeptoid material and the corresponding results are presented in Figure a. It was reported that the suitable solvent for the Li–S cell electrolytes is limited such as dimethyl ether (DME) and 1,3-dioxolane (DOL) used commonly. , It was seen that both DME and DOL electrolytes lead to synergistic effects on the retention capacity and specific capacity of sulfur as compared to the solvent alone . Because of this, we have investigated the binding energies of commonly used electrolytes (DOL and DME) with LiPS species.…”
Section: Resultsmentioning
confidence: 99%
“…In early stages, the main strategy for limiting the shuttle effect of LiPSs was to introduce heteroatoms, metal oxides, metal sulfides, and metal nitrides that suppressed the shuttle effect to a certain extent (Fang et al, 2020). However, these are mostly inorganic bulk materials and only limited surface atoms can be used as trapping sites for LiPSs.…”
Section: Metal-organic Hybrid Electrocatalystsmentioning
confidence: 99%